A BIBLIOMETRIC ANALYSIS OF AWE IN ACADEMIC WRITING: INSIGHT FROM THE SCOPUS DATABASE - Hana Nur Hanifah; Muhamad Taufik Hidayat; Wahid Hasim (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study investigates the development and research trends of Automated Writing Evaluation (AWE) in academic writing through a bibliometric approach. A total of 75 documents were retrieved from the Scopus database, covering publications between 2015 and 2025, and were analyzed using VOSviewer. The analysis focused on three dimensions: (1) publication trend analysis to chart the growth of AWE scholarship over time; (2) keyword co-occurrence analysis to identify dominant concepts and thematic clusters; and (3) thematic mapping to reveal emerging research directions and future opportunities. The findings reveal a marked upward trend in AWE research output, with publication volume remaining modest between 2015 and 2021 before rising sharply from 2022 onward, culminating in 22 documents in 2025 alone. Keyword analysis identified "automated writing evaluation" as the central concept (occurrences = 34; Total Link Strength = 96), closely networked with "feedback" (TLS = 38), "artificial intelligence" (TLS = 36), "ChatGPT" (TLS = 35), and "natural language processing" (TLS = 30). Three major thematic clusters were identified: a technology-oriented cluster encompassing AI and NLP tools; a feedback and assessment cluster centered on the pedagogical functions of AWE; and a language learning cluster foregrounding applications in second language (L2) and EFL academic writing contexts. The results further reveal a fundamental transition shifting from conventional automated scoring systems toward more sophisticated, AI-powered formative feedback mechanisms. These findings advance a more structured understanding of the intellectual landscape of AWE research in academic writing and identify concrete directions for future inquiry. ABSTRAK Penelitian ini mengkaji perkembangan dan tren penelitian Evaluasi Tulisan Otomatis (Automated Writing Evaluation/AWE) dalam penulisan akademik melalui pendekatan bibliometrik. Sebanyak 75 dokumen diperoleh dari basis data Scopus, mencakup publikasi antara tahun 2015 dan 2025, dan dianalisis menggunakan VOSviewer. Analisis difokuskan pada tiga dimensi: (1) analisis tren publikasi untuk memetakan pertumbuhan penelitian AWE dari waktu ke waktu; (2) analisis ko-kemunculan kata kunci untuk mengidentifikasi konsep dominan dan kluster tematik; dan (3) pemetaan tematik untuk mengungkap arah penelitian yang sedang berkembang dan peluang di masa mendatang. Temuan menunjukkan tren peningkatan signifikan dalam output penelitian AWE, dengan volume publikasi yang tetap moderat antara 2015 dan 2021 sebelum meningkat tajam sejak 2022, dengan puncaknya 22 dokumen pada tahun 2025. Analisis kata kunci mengidentifikasi "automated writing evaluation" sebagai konsep sentral (kemunculan = 34; Total Link Strength = 96), yang terhubung erat dengan "feedback" (TLS = 38), "artificial intelligence" (TLS = 36), "ChatGPT" (TLS = 35), dan "natural language processing" (TLS = 30). Tiga kluster tematik utama teridentifikasi: kluster berorientasi teknologi mencakup alat AI dan NLP; kluster umpan balik dan penilaian berpusat pada fungsi pedagogis AWE; dan kluster pembelajaran bahasa menonjolkan penerapan dalam konteks penulisan akademik bahasa kedua (L2) dan EFL. Hasil penelitian mengungkap transisi mendasar dalam bidang ini, dari sistem penilaian otomatis konvensional menuju mekanisme umpan balik formatif berbasis AI yang lebih canggih. Temuan ini berkontribusi pada pemahaman yang lebih terstruktur tentang lanskap intelektual penelitian AWE dalam penulisan akademik.